Analysis of Financial Performance Profitability of PT Unilever Indonesia 2014-2023 - Andi Maghfirah Zainal; Agusdiwana Suarni; Abdul Khaliq (IECON, 2024)
Purpose: This study aims to analyze the financial performance, specifically the profitability, of PT Unilever Indonesia Tbk, using profitability ratios such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Method/Methodology/Approach: This research employs statistical analysis using SPSS 26 to perform descriptive statistical analysis of profitability ratios, including ROA, ROE, and NPM, by processing secondary data from the annual financial reports of PT Unilever Indonesia Tbk for the period from 2014 to 2023. Findings: The analysis results indicate that the average profitability performance of PT Unilever Indonesia Tbk during 2014-2023 is reflected by an average ROA of 35.80% (standard deviation 5.554%), ROE of 133.10% (standard deviation 8.595%), and NPM of 16.20% (standard deviation 2.700%). The time series data show a downward trend in ROA from 40.18% (2014) to 28.81% (2023). Similarly, NPM declined from 16.62% to 12.43%. However, ROE increased from 124.78% to 141.98%, with the highest profitability recorded in 2020 at 145.08% before a subsequent decline in the following years. Practical Implications: This research provides an overview of the company's operational efficiency that needs to be improved, particularly in asset and cost management, although shareholder capital management remains effective. Originality/Value: This study provides a comprehensive analysis of profitability trends of one of the largest FMCG companies in Indonesia over the last decade, which can serve as a reference for investors and stakeholders in making investment decisions.